Factors that influence non-muslim domestic tourists’ intention to consume halal foods in Malaysia - Nur Bashiratul Khalidah Ismail Hisyam; Nur Cahaya Ot Ator; Nurul Atiqah Abdul Hafiz; Yang Hui Fong (2021)
As a multi-racial country with Muslim is the majority, halal food among non-Muslim in Malaysia become significant to be studied. Muslims usually used the concept of halal. To ensure health care, non -Muslims have the potential to be targeted by halal food businesses. They misunderstood the concept of halal as a religious value only. In fact, it represents the cleanliness, health and quality of the food eaten. The results show that non-Muslims can be the target market for the halal food industry. The aim of the study is to investigate the factors that influence non-Muslim domestic tourist intention to consume halal food in Malaysia. This study examines whether health consciousness, attitude, and halal awareness influence non-Muslim domestic tourist’s intention to consume halal food in Malaysia. This quantitative research used online survey distributed using convenience sampling through the media social for example Facebook, WhatsApp, Telegram and Twitter targeting non-Muslims domestic tourist in Malaysia. There has a 363 data were gathered and analyzed using SPSS version 2020 for descriptive, reliability and correlation analysis to answer the research objectives. Among the three variable, health consciousness is the most significant factors followed by attitude and halal awareness is the least factor that contribution to intention to consume halal food in Malaysia among non- Muslim domestic tourist. The result shows health consciousness, attitude and halal awareness are significant factors that influenced intention to consume halal food among non-Muslim domestic tourist in Malaysia. This study contributes to added knowledge in the factors that contribute to non-Muslim domestic tourist intention to consume halal food while travelling locally.